6x+3y=2(3y+x)+4

Simple and best practice solution for 6x+3y=2(3y+x)+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+3y=2(3y+x)+4 equation:


Simplifying
6x + 3y = 2(3y + x) + 4

Reorder the terms:
6x + 3y = 2(x + 3y) + 4
6x + 3y = (x * 2 + 3y * 2) + 4
6x + 3y = (2x + 6y) + 4

Reorder the terms:
6x + 3y = 4 + 2x + 6y

Solving
6x + 3y = 4 + 2x + 6y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
6x + -2x + 3y = 4 + 2x + -2x + 6y

Combine like terms: 6x + -2x = 4x
4x + 3y = 4 + 2x + -2x + 6y

Combine like terms: 2x + -2x = 0
4x + 3y = 4 + 0 + 6y
4x + 3y = 4 + 6y

Add '-3y' to each side of the equation.
4x + 3y + -3y = 4 + 6y + -3y

Combine like terms: 3y + -3y = 0
4x + 0 = 4 + 6y + -3y
4x = 4 + 6y + -3y

Combine like terms: 6y + -3y = 3y
4x = 4 + 3y

Divide each side by '4'.
x = 1 + 0.75y

Simplifying
x = 1 + 0.75y

See similar equations:

| 72=-2(-3x) | | 4(w-4)=48 | | x^2+10x+15=18 | | -x(0)+3y=6 | | ln(5x-1)=ln(2x+8) | | -2.4x-10.25=1.75 | | 5x^2+14x-2=0 | | -x+3(0)=6 | | a*x^2-(a-b)*x=0 | | r=x^4cos(x) | | 1000/400 | | 5X-20=21-7X | | -5x+7=0+2x | | 5(m-2)=30 | | (4-i)/(6-2i) | | 1000/400x | | 9(d-5)=90 | | (0)=-2x+1 | | y=-2(0)-8 | | y=-2x^2-12x+22 | | 7x-15=10x+8 | | 10x+1=15-5x | | 16(p+2)=32 | | 2x^2-12-1=0 | | 9x-2y=40 | | 4x+1+3x=-83 | | 3.6x-2.25=15.75 | | 30/5=5x | | 8(0)-6y=48 | | 5x+12y=148 | | 80x^5=20x^2 | | 80x^5=20x^3 |

Equations solver categories